(ii) Interim report on the inscriptions from the aedes of the fort near Tel Shalem. (2019) - Ecker, Avner; Arubas, Benjamin; Heinzelmann, Michael; Mevorah, David
Abstract : Ever since the discovery of a building inscription of a vexillatio of the legio VI Ferrata near Tel Shalem, 1 it was clear that the area was a locus of Roman military activity. In the following years the vicinity of the Tel yielded the inscription of a Hadrianic arch whose letter-size is surpassed only by the lettering on the Pantheon and the Arch of Titus in Rome. 2 Most recently, the headquarters complex of the fort ( principia ), and in particular the regimental shrine ( aedes or sacellum ), have been uncovered (see above). Within and in front of the aedes were found three inscriptions: 3 a dedicatory inscription to Caracalla on a statue base in front of the building (no. 1), and two mosaic inscriptions inside, one at the entrance to the nave (no. 2), the other at its far end (no. 3). The fills covering the building produced stamped roof-tiles bearing three different formulae. The new inscriptions prove that the building was the aedes of the Ala VII Phrygum . The earliest attestation of its presence in Syria Palaestina is inferred from a military diploma ofA.D . 139 4 found at Apheka, not far from Tel Shalem. Assuming that the Ala Phrygum, attested without the number VII in the province of Syria up toA.D . 88, 5 is the same unit as the Ala VII Phrygum of our inscriptions, its transfer to Iudaea is most likely to be associated with the suppression of the Bar Kokhba Revolt. 6 The inscriptions published here provide the latest known date for its stay in Syria Palaestina, some 40 years after the latest date so far attested in military diplomas. 7